Indigenous Australian Content in Bachelor of Social Work Degrees: Detailed Description - Nipperess, Joe; Baldry, Eileen (UNSW Sydney, 1998)
The following report is a detailed description of the Indigenous Australian content of thirteen BSW courses offered at various Australian Universities. The content descriptions were collected and summarised by Joe Nipperess, a fourth year social work student, from information kindly sent by various staff members at those universities and was checked back with those staff members for accuracy. Most of the respondents returned the material with some changes which were incorporated; a small number did not reply. There may be some inaccuracies therefore in some segments. If so, please accept our apologies. Please inform us of any changes needed.